Analisa Kandungan N,P,K Dan C Organik pada Tanah Top Soil di Wilayah Dataran Tinggi Kebun Bah Birong Ulu Ptpn Iv Regional II - Guk Guk, Andreas S.M Raja; Manurung, Saroha; Djaingsastro, Aulia Juanda (Lembaga Teewan Journal Solutions, 2026)
Soil fertility is one of the main factors affecting oil palm productivity, particularly in highland areas with varying topographic conditions. Differences in land slope are believed to influence the distribution of soil nutrients due to erosion and nutrient leaching. This study aims to analyze the content of nitrogen (N), phosphorus (P), potassium (K), organic carbon, and topsoil pH on flat and sloping land at the Bah Birong Ulu Plantation, PTPN IV Regional II. The study employs a quantitative approach using field survey methods and descriptive analysis. Soil samples were collected from flat and sloping land using a soil auger at several observation points. Laboratory analysis was conducted to determine nitrogen content using the Kjeldahl method, phosphorus using the antimony molybdate colorimetric method, potassium using flame photometry, organic carbon using the Walkley and Black method, and pH measurement using a pH meter. The research data were analyzed using a two-sample t-test under the assumption of unequal variances. The results of the study indicate that there are no statistically significant differences in the nitrogen, phosphorus, potassium, organic carbon, and soil pH levels between flat and sloped land. The average nitrogen content in sloped soil was 0.53% and in flat soil was 0.50%, organic carbon content was 1.37% and 1.17%, respectively; phosphorus content was 33.45 ppm and 37.65 ppm; potassium content was 0.637 me/100 g and 0.611 me/100 g; and soil pH was 5.34 and 5.80. These results indicate that topographic conditions have not yet had a significant effect on the distribution of soil nutrients at the study site. This study concludes that plantation management practices such as fertilization, soil conservation, and organic matter management have a greater influence than land slope conditions in maintaining soil nutrient stability. It is hoped that these findings will serve as a basis for developing more effective soil fertility management strategies and fertilization recommendations for oil palm plantations in highland areas.